Efficacy of 810-nm diode laser transpupillary thermotherapy delivered using the methodology developed for small (T1) choroidal melanomas - I.V. Tsukanova; S.I. Poliakova; V.O. Naumenko; N.V. Pasyechnikova (Ukrainian Society of Ophthalmologists, 2019)
Background: Diode laser transpupillary thermotherapy (TTT) used as a monotherapy may be a treatment of choice for small choroidal melanomas (CM). We developed the methodology for performing TTT, which involves four sessions delivered daily over four consecutive days (Information Bulletin No. 22, based on Pat. of Ukraine №102,890 issued 25.11.2015. Method for treatment of T1 choroidal melanoma), and which we have been using for the treatment of small (T1) CM (measuring ≤ 3 mm in thickness and ≤ 12 mm in basal dimension) for 15 years. Purpose: To assess the efficacy of 810-nm diode laser TTT delivered using the developed methodology in small tumors differing in magnitude of baseline characteristics. Materials and Methods: We assessed the efficacy of 810-nm diode laser TTT delivered using the developed methodology for the small (T1) CM (measuring ≤ 3 mm in protrusion into the vitreous and ≤ 12 mm in basal dimension). Eighty-eight patients (63 men (71.6%) and 25 women (28.4%); mean age, 55.9 (12.8) years (range, 23 to 82 years) with small (T1) CM were involved into the study. The right eye was affected in 41 cases (46.6%), and the left eye was affected in the other 47 cases (53.4%). At baseline, no patient had metastasis. Treatment outcome was categorized as positive if partial or complete scarring of the tumor site was observed or negative if tumor growth persisted. Results: Eighty-one patient (92.05%) reached a positive treatment outcome, and 7 (7.95%) had a negative treatment outcome. In addition, complete scarring or partial scarring was found in 81.5% and 18.5%, respectively, of those with a positive treatment outcome. The treatment outcome in patients even with small (T1) CM (measuring ≤ 3 mm in thickness and ≤ 12 mm in basal dimension) depended on tumor dimensions and tumor area at baseline. Patients with small CM of more than 2.18-mm protrusion into the vitreous, more than 8.45-mm basal dimension, and more than 66.6 mm2 tumor area were 2.80 times more likely to have a negative treatment outcome. Conclusion: We developed the methodology for performing TTT, which involves four sessions delivered daily over four consecutive days (Information Bulletin No. 22, based on Pat. of Ukraine №102,890 issued 25.11.2015. Method for treatment of T1 choroidal melanoma) for the treatment of small (T1) CM (measuring ≤ 3 mm in thickness and ≤ 12 mm in basal dimension). The success rate of the TTT methodology developed for small (T1) CM (measuring ≤ 3 mm in thickness and ≤ 12 mm in basal dimension) was 92.05%. The efficacy of treatment of small (T1) CM depended on tumor parameters at baseline: patients with a small CM measuring < 2 mm in thickness, < 8 mm in basal dimension, and < 66 m2 in area were more likely to have a positive treatment outcome in the form of scarring of the tumor site in 81.5% of cases.